1973
DOI: 10.1071/bi9730645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage of Rabbit Spermatozoa at?79°C on Their Subsequent Transport and Fertility in the Rabbit Doe

Abstract: Twenty-four does were inseminated with either 3 x 10 6 or 30 X 10 6 motile spermatozoa, either recently collected or after storage at -79°C. The females were killed 18 hr after insemination, and ova and spermatozoa recovered from their reproductive tracts. Fewer spermatozoa were recovered from does inseminated with 3 x 10 6 than with 30 x 10 6 motile sperm. There was no significant difference between fresh and stored semen in numbers of spermatozoa recovered.The number of sperm in the oviducts was small; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Although no reduction in sperm motility was found, fewer spermatozoa were seen in the mucin coat and zona pellucida of embryos recovered from does inseminated with spermatozoa frozen for 5 hr. Murdoch & O'Shea (1973) previously reported that fewer supplementary spermatozoa were associated with ova recovered from does inseminated with frozen spermatozoa than those from does inseminated with fresh semen. Freezing and thawing of mammalian cells have been reported to damage mitochondria, ribosomes, lysosomes, and the endoplasmic reticulum (Tappel, 1966;Quinn & White, 1966;Quinn, White & Cleland, 1969), The loss and return of the fertilizing ability of frozen spermatozoa might have been due to a time-related repair of damage caused by the freezing process and/or ice crystal formation changes with time causing less cellular damage during thawing (Rapatz & Luyet, 1961).…”
Section: Effects On Fertilizationmentioning
confidence: 96%
“…Although no reduction in sperm motility was found, fewer spermatozoa were seen in the mucin coat and zona pellucida of embryos recovered from does inseminated with spermatozoa frozen for 5 hr. Murdoch & O'Shea (1973) previously reported that fewer supplementary spermatozoa were associated with ova recovered from does inseminated with frozen spermatozoa than those from does inseminated with fresh semen. Freezing and thawing of mammalian cells have been reported to damage mitochondria, ribosomes, lysosomes, and the endoplasmic reticulum (Tappel, 1966;Quinn & White, 1966;Quinn, White & Cleland, 1969), The loss and return of the fertilizing ability of frozen spermatozoa might have been due to a time-related repair of damage caused by the freezing process and/or ice crystal formation changes with time causing less cellular damage during thawing (Rapatz & Luyet, 1961).…”
Section: Effects On Fertilizationmentioning
confidence: 96%
“…IV), which was in agreement with the results reported by Maurer et al [9], who observed a 45% cleavage rate (from total recovery) when inseminating with frozen sperm. The low number of total embryos recovered could indicate a problem in the transport of sperm (very few sperm are able to reach the oviducts to fertilise oocytes, although Murdoch and O'Shea, [12], observed fewer sperm in the oviducts of females inseminated with frozen sperm, but the differences between fresh and frozen sperm were not significant) since other authors have reported fewer accessory sperm in oocytes from females inseminated with frozen sperm [9,12,14]. This could also indicate a very low viability of the spermatozoa (they could reach the oviducts, but they would remain alive for a very short time) or any other problems which could 195 …”
Section: Discussionmentioning
confidence: 99%
“…Early attempts to achieve fertilization with rabbit semen frozen and thawed in the presence of glycerol were relatively unsuccessful, but better results were achieved using ethylene glycol (Fox & Burdick, 1963) or dimethylsulphoxide (Sawada & Chang, 1964) as cryoprotective agents. High kindling rates with frozen rabbit semen have been documented and observations have been made on several factors relating to rabbit semen freezing, such as sperm numbers for inseminations (Andrieu & Courot, 1976), acrosome morphology (Weitze, Hellemann & Krause, 1976;Hellemann, 1977), storage periods (O'Shea & Wales, 1969;Maurer, Stranzinger & Paufler, 1976), sperm transport in the female reproductive tract (Murdoch & O'Shea, 1973) and freezing procedures (Stranzinger, Maurer & Paufler, 1971;Weitz et al, 1976). However, no cryoprotective agents other than glycerol, dimethylsulphoxide and ethylene glycol have been examined for the low temperature preservation of rabbit semen.…”
Section: Introductionmentioning
confidence: 96%